2018
DOI: 10.1055/s-0038-1642607
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Cochlear Implantation in Children with Multiple-handicaps: Parent's Perspective

Abstract: Introduction  The cochlear implants centers in the world are studying the cochlear implantation in children with multiple handicaps. Objective  To develop a questionnaire to analyze the subjective benefits of the cochlear implantation in multiple handicapped children according to their parent's perspective. Methods  A questionnaire was applied to 14 families of multiple handicapped children, aging from 2–12 years old and having from 11 months to 11 years of implant use. Results  The social-emotional abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
(46 reference statements)
2
23
0
3
Order By: Relevance
“…Study populations ranged from 2 months old to 18 years old participants. Ten studies included both preschool- and school-aged children ( 32 , 37 38 , 44 , 48 49 , 53 , 56 57 , 62 ). Twenty-eight studies explicitly included either preschoolers ( 5 , 27 29 , 30 31 , 33 36 , 39 40 ) or school-aged children ( 38 , 41 43 , 46 47 , 50 – 52 , 54 55 , 58 61 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study populations ranged from 2 months old to 18 years old participants. Ten studies included both preschool- and school-aged children ( 32 , 37 38 , 44 , 48 49 , 53 , 56 57 , 62 ). Twenty-eight studies explicitly included either preschoolers ( 5 , 27 29 , 30 31 , 33 36 , 39 40 ) or school-aged children ( 38 , 41 43 , 46 47 , 50 – 52 , 54 55 , 58 61 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the other six studies, the age range was not reported, however mean age was provided frequently ( 5 , 27 , 31 , 42 , 52 , 56 ). Six studies provided outcomes of social competence only ( 28 , 30 , 36 , 44 , 53 , 59 ), 13 studies provided emotional functioning only ( 5 , 31 , 35 , 37 , 42 43 , 48 , 52 , 54 55 , 58 , 61 , 63 ), whilst the remaining 19 studies provided a combination of social competence and emotional functioning for pre-school children ( 27 , 29 , 32 – 34 , 38 40 ) and school-aged children ( 38 , 41 , 46 47 , 49 51 , 56 57 , 60 , 62 ). Tables 3 and 4 included a comprehensive summary of studies including the authors, measures, research designs, samples, findings and limitations of the described socio-emotional development among children with CI.…”
Section: Resultsmentioning
confidence: 99%
“…Disabilities There were six studies that presented data on speech and language scores in children with ASD and additional disabilities (20,23,24,35,36,42). These studies…”
Section: Outcomes In Children With Asd and Additionalmentioning
confidence: 99%
“…Epidemiological studies estimate that as many as 40% of hearing-impaired children have an additional need for CI [ 2 ]. Cochlear implantation has a positive impact on the quality of life in deaf children, which not only bring improved social-emotional abilities to the profoundly deaf children but also help improve attention span and adherence to other therapies and school activities [ 3 , 4 ]. However, it is still a challenge to evaluate postintervention rehabilitation for pediatric hearing-impaired patients receiving cochlear implant.…”
Section: Introductionmentioning
confidence: 99%